Changes In Vitamin C and Total Microbes Of Papaya Fruit (Carica papaya L.) Which Is Processed Minimally Using Edible Coating Of Agar-agar Based On The Storage Time - Liya Apriani; Siti Aminah; Joko Teguh Isworo (Universitas PGRI Semarang, 2020)
Minimal processing and edible coatings began to be known to provide food security and improve the quality of food products at the time of storage. This study was to determine the effect of minimal processing using agar-agar based on storage time to changes in vitamin C and total microbes papaya (Carica papaya L.).This research is an experimental laboratory study with the research design used is a two-factor Randomized Completely Design (CRD). The number of units used in the study was 28 samples followed by samples without agar coating. Data on vitamin C were measured by the iodimetry method, total microbes by the Total Plate Count (TPC) method. The statistical test used was the Two Way Anova. There are differences in the results of tests of vitamin C levels, total microbes and weight loss between the treatment and control groups. There is a minimal processing effect using agar-agar on vitamin C levels (ρ = 0.006) and total microbes (ρ = 0,000). Minimal processing using agar-agar coatings based on long storage effect on the levels of vitamin C and total microbes papaya (Carica papaya L.)